Determining Controlling Functions in the Enterprise Management Activity - Firsova, S.N. (Економічний вісник Донбасу, 2013)
The article considers and determines the localization of controlling in the system of business management as a central subsystem. Functions, tasks, spheres of application and objects of controlling are specified. The presented classification determines the role of controlling in the company activity. Based on the scientific analysis, basic functions of controlling are systematized as a classifier of basic managerial functions.